A casework study: The effect of the porcine digestive process on animal carcasses and human teeth. (April 2023) - Atwood, Lauren; Lain, Russell; Kotzander, Jessica; McCardle, Penny; Mason, Brett; Raymond, Jennifer; Sears, Alison
Abstract: What happens if a human body is fed to pigs? Although a popular notion in the entertainment industry, no scientific published literature exists that documents this porcine feeding behaviour, nor, more importantly, what elements of the cadaver may survive such a process. A study conducted in 2020, born out of a casework enquiry, aimed to investigate the following two questions; Would pigs feed on a human body? And, if so, what could be recovered post feeding event? Kangaroo carcasses, porcine carcasses (as human analogues) and 90 human teeth were prepared, and fed, to two domestic pigs, in a variety of feed scenarios. Biological traces including bones, bone fragments, teeth and tooth fragments were recovered both post-digestion from the faeces of the pigs, as well as uneaten from the porcine enclosure. 29% of all human teeth were recovered from the study; 35% of which were recovered post-digestion from the faeces and 65% were recovered uneaten from the porcine enclosure, Of the recovered human teeth, 81% were deemed suitable for identification by a forensic odontologist. From the 447 bones recovered from the enclosure, 94% could be identified to a bone type and species. From all 3338 bone fragments recovered from the faeces of the pigs, none retained any morphological traits that would allow further intelligence to be generated. Overall, it was found that pigs will feed on human analogues and will consume soft tissue, bones, and human teeth. Biological traces in the form of bones, bone fragments, teeth and tooth fragments may be recovered both post-digestion from the faeces, or from the porcine enclosure. The biological traces can be used for identification of an individual via forensic odontology, identification of a species via forensic anthropology and may be suitable for DNA analysis. The outcomes of this study generated new avenues for investigation in the case and may be used to inform future operational resources. Highlights: Pigs will eat and digest bones, teeth, and flesh of human analogues. Human teeth and bones can be recovered post porcine digestion. Recovered human teeth can be used for identification via forensic odontology.